2018
DOI: 10.1016/j.canep.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and colorectal cancer risk in Zimbabwe: A population based case-control study

Abstract: HighlightsThree main dietary patterns in Zimbabwe; traditional African, urban and processed foods.Traditional African diet associated with a reduced risk of colorectal cancer.No association between colorectal cancer and the urban or processed food patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
3
20
0
1
Order By: Relevance
“…The high levels in both study groups are consistent with a diet that is predominatly plant based, but significantly lower levels in the urban participants may indicate an initial adaptation of the gut microbiota to dietary changes associated with urban lifestyle. We have previously shown that a traditional African diet, which is predominatly plant based, and associated with rural lifestyle, correlates with lower incidence of CRC in this population (27). We also detected significantly higher levels of Streptococcus bovis et rel.…”
Section: Discussionsupporting
confidence: 58%
“…The high levels in both study groups are consistent with a diet that is predominatly plant based, but significantly lower levels in the urban participants may indicate an initial adaptation of the gut microbiota to dietary changes associated with urban lifestyle. We have previously shown that a traditional African diet, which is predominatly plant based, and associated with rural lifestyle, correlates with lower incidence of CRC in this population (27). We also detected significantly higher levels of Streptococcus bovis et rel.…”
Section: Discussionsupporting
confidence: 58%
“…De siete estudios que evaluaron riesgo de cáncer de mama 19,26,27,28,29,30,31 , cuatro encontraron una asociación positiva. Así también, dos de tres estudios que evaluaron cáncer colorrectal encontraron mayor riesgo de cáncer 19,32,33 . Además, tres estudios evaluaron cáncer de próstata 19,34,35 , dos cáncer esofágico 36,37 , uno cáncer de tiroides 38 , uno cáncer hepático 39 , uno cáncer de pulmón 29 , uno leucemia linfocítica crónica 40 , uno cáncer gástrico 41 y uno mortalidad por cáncer 42 .…”
Section: Resultsunclassified
“…In a more global world, the introduction of a Western diet with a high consumption of red processed meet or high glycaemic load carbohydrates with low intake of fruits and vegetables coupled with rising obesity, alcohol consumption and cigarette smoking may result in an increased risk of CRC in low middle income countries to the level seen in high income countries [4,[9][10][11][12]. It is difficult to unravel the relative contributions and interactions of each of these factors to an increased risk of CRC.…”
Section: Possible Reasons Behind the Rise In Incidence Of Crc In Ugandamentioning
confidence: 99%